ACCOUNTABILITY OF PUBLIC SERVICES IN THE IMPLEMENTATION OF BUILDING PERMITS (CASE STUDY AT THE MAKASSAR CITY INVESTMENT AND ONE-STOP INTEGRATED SERVICES OFFICE) - Khaer, Ummul; Guntur, Muhammad; Darwis, Muh (Universitas Negeri Makassar, 2025)
This study aims to determine Public Service Accountability in the Implementation of Building Permits (Case Study at the Makassar City Investment and One-Stop Service Office). This research includes descriptive qualitative research with data collection techniques through observation, interviews, literature study and documentation. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The results of the study show that Public Service Accountability in the Implementation of Building Permits (Case Study at the Makassar City Investment and One-Stop Services Office) is based on process accountability indicators according to Sheila Elwood (Raba, 2006), namely: 1) Compliance with procedures, 2) Public services with cost certainty, 3) Compliance with time standards, 4) Responsive public services, that in general are not fully accountable in providing services. This is based on that service references are not fully oriented to the service user (public/applicant), this can be seen from the length of time for issuance of the IMB and the priority of the applicant's interests are not fully prioritized because the applicant sometimes waits because the certainty of the IMB processing time is not informed and the officer concerned sometimes not in place.